Towards a Logic of Encounter: Social Art in the Framing of an International Conflict Transformation Initiative - Bleuler, Marcel (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Since the early 21st century, there has been a growing number of alliances between social art and so-called international ‘development’ cooperation and NGO work. Scholars mostly discuss such alliances from a perspective that expects art projects to result in conclusive effects. This paper argues that such an effect-oriented perspective is based on a reductive notion of art and that it fails to notice the self-critical principles that social art contributes to the field of international cooperation. Based on a detailed discussion of the continuing project off/line: what can art do in Zemo Nikozi? (since 2016), which invites artists to work in the framing of a long-term engagement for conflict transformation in the Shida Kartli region of Georgia, this paper presents concrete processes of social art and differentiates them according to how they relate to the implementation context. On this basis, the paper conceptualizes social art practices as process-oriented spaces of encounter, and draws conclusions on a discursive logic that complements the effect-oriented discourse.